SBS modifier and preparation method and application thereof, asphalt coating material composition and preparation method thereof, and waterproof coiled material
Thiol grafting and reaction with biomass carbon aerogel create a stable SBS modifier that maintains asphalt waterproofing membrane performance over time by addressing separation and aging issues.
Patent Information
- Application Number
- CN202411429962.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-14
AI Technical Summary
SBS modifiers separate from asphalt during long-term storage due to structural and molecular differences, leading to substandard performance and reduced aging resistance in asphalt waterproofing membranes.
Thiol grafting is used to modify SBS to match its polarity with asphalt, and then react it with biomass carbon aerogel to form a stable macromolecular compound, preventing performance attenuation during aging.
The modified SBS modifier maintains long-term stability and durability of asphalt waterproofing membranes by preventing phase separation and enhancing aging resistance.
Smart Images

Figure BDA0005083665320000111 
Figure BDA0005083665320000211 
Figure HDA0005083665350000011
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of waterproof materials, and in particular relates to an SBS modifier and a preparation method and use thereof, an asphalt coating composition and a preparation method thereof, and a waterproof roll. Background Art
[0002] At present, thermoplastic elastomer polystyrene-butadiene-styrene triblock copolymer (SBS) is the most commonly used asphalt modifier in asphalt waterproofing membranes, which has a significant improvement on the high-temperature aging resistance and low-temperature bending resistance of asphalt. However, there are differences between the matrix asphalt and SBS in terms of structure, molecular weight, polarity, etc., which causes the SBS modifier and asphalt to separate during long-term storage of SBS-modified asphalt, resulting in the problem of substandard performance after 3 months or more. In addition, the polybutadiene segment (PB segment) of SBS contains double bonds, so the presence of unsaturated bonds will cause it to react easily with oxygen during long-term aging, and the aging resistance will drop sharply. In view of this, researchers have proposed a technical solution for chemically modifying SBS to improve the aging resistance of asphalt. Common methods for chemical modification of SBS include catalytic hydrogenation, grafting modification, epoxidation modification, sulfonation modification, halogenation modification, thiol click reaction and other methods.
[0003] The existing method for preparing SBS modified asphalt discloses that a stabilizer is prepared by an esterification reaction between a styrene-maleic anhydride copolymer and a long-chain alcohol under acid catalysis, and then the stabilizer is adsorbed on the polystyrene and asphaltene macromolecules of SBS through physical action, thereby enhancing the dispersion effect of the light components in the asphalt on SBS and asphaltene, so that the SBS modified asphalt has long-term thermal storage stability. Although this method achieves the effect of modifying asphalt, it does not have long-term stability compared to the structure formed by chemical reactions during the long-term storage of asphalt. The prior art also discloses an asphalt modifier, which uses vinyl trimethoxysilane as a cross-linking agent and dibenzoyl peroxide as an initiator to cross-link SBS polymer, maleic anhydride and methyl methacrylate to prepare modified SBS. Although this method improves the adhesion effect of the SBS polymer and enhances the bonding force between the SBS modifier and the asphalt, the preparation process is relatively cumbersome. Summary of the invention
[0004] The embodiment of the present application provides an SBS modifier and a preparation method thereof, wherein the polarity of SBS is changed by thiol grafting to SBS to make it closer to the polarity of asphalt, and then reacted with biomass carbon aerogel to generate a macromolecular compound with a relatively stable structure, thereby preventing the performance of the asphalt waterproofing membrane containing the SBS modifier from being significantly attenuated during the long-term aging process.
[0005] In a first aspect, the present application provides a method for preparing an SBS modifier, comprising: dissolving SBS in a first solvent to obtain an SBS solution; adding a thiol compound to the SBS solution, and performing solution graft polymerization at a temperature of 50°C to 90°C to obtain a grafted modified SBS, wherein the grafted modified SBS is obtained by grafting an alkyl group containing at least one of a hydroxyl group and a carboxyl group with a thiol group, or by grafting a thiol group and grafting a hydroxyl-substituted or unsubstituted alkyl group with a thiol group; adding biochar aerogel and the grafted modified SBS to a second solvent in a mass ratio of 1:(0.5 to 1.5) to obtain a first mixed solution; adding concentrated sulfuric acid and sodium hypophosphite to the first mixed solution, and reacting at a temperature of 120°C to 130°C to obtain an SBS modifier.
[0006] According to an embodiment of the first aspect of the present application, SBS has a linear structure, and the weight average molecular weight of SBS (ethylene-butadiene-styrene triblock copolymer) is 100,000 to 450,000.
[0007] According to an embodiment of the first aspect of the present application, the weight average molecular weight of SBS is 150,000 to 300,000.
[0008] According to the embodiment of the first aspect of the present application, the content of styrene segments in SBS is 20% to 30%; and the melt flow rate is 0 g / 10 min to 1 g / 10 min.
[0009] According to an embodiment of the first aspect, the first solvent is selected from at least one of toluene, cyclohexane, CCl4, and CHCl3.
[0010] According to an embodiment of the first aspect of the present application, in the process of dissolving SBS in the first solvent, the temperature of the first solvent is increased to 30° C. to 50° C. to accelerate the dissolution rate of SBS.
[0011] According to an embodiment of the first aspect of the present application, a thiol compound is added to the SBS solution, and solution graft polymerization is carried out using an initiator at a temperature of 50° C. to 90° C.
[0012] According to an embodiment of the first aspect, the amount of the initiator added is 0.5 wt% to 3 wt% of the mass of the SBS. The initiator is azobisisobutyronitrile. Optionally, the amount of azobisisobutyronitrile added is 0.5 wt% to 2 wt% of the mass of the SBS.
[0013] According to an embodiment of the first aspect, a grafted modified SBS is prepared by the following steps: dissolving SBS in a first solvent under an inert atmosphere to obtain an SBS solution; adding a thiol compound and an initiator to the SBS solution, heating the solution to 50°C to 90°C for solution graft polymerization to obtain a grafted modified SBS.
[0014] According to an embodiment of the first aspect, a thiol compound and an initiator are added to an SBS solution and the temperature is raised to 50° C. to 90° C. to perform solution graft polymerization to obtain a modified SBS mixed solution.
[0015] According to an embodiment of the first aspect of the present application, the step of preparing the graft-modified SBS further includes: dropping the modified SBS mixed solution into methanol for purification to prepare the graft-modified SBS.
[0016] According to an embodiment of the first aspect, the mass ratio of SBS to the thiol compound is 20:(5-15).
[0017] According to an embodiment of the first aspect, the thiol compound is selected from at least one of mercaptoethanol, n-dodecyl mercaptan, and mercaptopropionic acid.
[0018] According to an embodiment of the first aspect of the present application, biomass carbon aerogel and grafted modified SBS are added to a second solvent at a mass ratio of 1:(0.5-1.5) and the temperature is raised to 50°C-90°C.
[0019] According to an embodiment of the first aspect, the second solvent is selected from dimethyl sulfoxide (DMSO) and dimethylformamide (DMF).
[0020] According to an embodiment of the first aspect of the present application, concentrated sulfuric acid and sodium hypophosphite are added to the first mixed solution, reacted at a temperature of 120° C. to 130° C., and heat-insulated under an inert atmosphere to obtain an SBS modifier.
[0021] According to the embodiment of the first aspect of the present application, concentrated sulfuric acid and sodium hypophosphite are added to the first mixed liquid, the reaction is carried out at a temperature of 120°C to 130°C, and the heat preservation treatment is carried out under an inert atmosphere. The process parameters that need to be met are: pressure of -80KPa to -50KPa, introduction of an inert atmosphere, and a heat preservation treatment time of 2.5 hours to 4 hours.
[0022] According to the embodiment of the first aspect of the present application, the biomass carbon aerogel in the step of obtaining the first mixed liquid is prepared by the following steps: mixing the wood material and water according to a preset ratio and performing hydrothermal treatment to obtain a first product; washing and freezing the first product to obtain a frozen product; and freeze-drying the frozen product to obtain the biomass carbon aerogel.
[0023] According to an embodiment of the first aspect of the present application, the wood material is selected from at least one of eucalyptus, pine, poplar, elm, willow, apricot, birch, maple, camphor and shrub chips.
[0024] According to an embodiment of the first aspect, the preset ratio of the wood material to water is 1:(5-10).
[0025] According to the embodiment of the first aspect of the present application, the process parameters for the hydrothermal treatment of the wood material and water need to meet the following requirements: reacting at 200° C. to 350° C. for 10 to 15 hours.
[0026] According to an embodiment of the first aspect, the freezing temperature of the first product is -40°C to -10°C, and the freezing time is 15 hours to 30 hours.
[0027] According to an embodiment of the first aspect, the inert atmosphere is formed by at least one selected from nitrogen, argon, and neon.
[0028] In a second aspect, the present application provides an SBS modifier prepared according to the above-mentioned method for preparing the SBS modifier.
[0029] In the third aspect, the present application provides an asphalt coating composition, including raw materials with rubber addition percentage: asphalt, 100PHR; asphalt softening oil, 5PHR~10PHR; SBS modifier, 3PHR~5PHR; SBS modifier is an SBS modifier prepared according to the preparation method of the above-mentioned SBS modifier; SBR modifier, 2PHR~4PHR; rubber powder, 30PHR~50PHR; powder, 50PHR~70PHR.
[0030] According to an embodiment of the third aspect, the asphalt is selected from 70# asphalt, 90# asphalt or a combination thereof.
[0031] According to an embodiment of the third aspect, the asphalt softening oil is at least one of cycloparaffinic oil, soybean oil, and aromatic oil.
[0032] According to an embodiment of the third aspect, the rubber powder is 60-80 mesh tire rubber powder, the rubber content is 30%-50%, and the ash content is 10%-30%.
[0033] According to an embodiment of the third aspect, the powder is selected from heavy calcium powder and talcum powder, and the particle size is 200 mesh to 400 mesh.
[0034] In a fourth aspect, the present application provides a method for preparing an asphalt coating composition, comprising: mixing asphalt and asphalt softening oil according to the ratio of the asphalt coating composition to obtain a first mixture; heating the first mixture until the asphalt is completely melted, adding an SBS modifier and an SBR modifier to the first mixture for dispersion to obtain a second mixture; adding rubber powder to the second mixture for dispersion to obtain a third mixture; adding powder to the third mixture for dispersion to obtain an asphalt coating composition.
[0035] According to an embodiment of the fourth aspect, the first mixture is heated to 130° C. to 150° C. to melt all the asphalt.
[0036] According to an embodiment of the fourth aspect, rubber powder is added to the second mixed material and the temperature is raised to 180° C. to 190° C. for dispersion.
[0037] According to an embodiment of the fourth aspect, powder is added to the third mixed material and dispersed at 180° C. to 190° C.
[0038] In a fifth aspect, the present application provides a waterproof roll material, comprising: a main substrate; an asphalt coating layer arranged on at least one side of the main substrate, the asphalt coating layer being formed by coating the above-mentioned asphalt coating composition on at least one side of the main substrate.
[0039] According to an embodiment of the fifth aspect, the waterproof membrane further includes an isolation protection layer covering the asphalt coating layer.
[0040] According to an embodiment of the fifth aspect, the main substrate is selected from polyester, fiberglass or polyester-fiberglass.
[0041] According to an embodiment of the fifth aspect, the isolation protection layer is a single-sided release film made of transparent PET material.
[0042] The preparation method of the SBS modifier of the embodiment of the present application is to graft SBS through thiol groups to change the polarity of SBS to obtain grafted modified SBS, so that the grafted modified SBS is closer to the polarity of asphalt; the grafted modified SBS is then reacted with biomass carbon aerogel to generate a macromolecular compound with a relatively stable structure, namely, the SBS modifier, to prevent the performance of the asphalt waterproofing membrane containing the SBS modifier from being significantly attenuated during the long-term aging process. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solution of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0044] Figure 1 Schematic diagram of the process for preparing the SBS modifier provided in the examples of the present application;
[0045] Figure 2 It is a schematic flow chart of a method for preparing an asphalt coating composition provided in the present application;
[0046] Figure 3 It is a schematic diagram of the structure of the waterproof membrane provided in an embodiment of the present application.
[0047] Explanation of the accompanying drawings: 1. Main substrate; 2. Asphalt coating layer; 3. Release protective layer. DETAILED DESCRIPTION
[0048] The features and exemplary embodiments of various aspects of the present application will be described in detail below. In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only intended to explain the present application, rather than to limit the present application. For those skilled in the art, the present application can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present application by illustrating the examples of the present application.
[0049] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "include..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.
[0050] As a commonly used asphalt modifier, SBS has a significant effect on improving the high-temperature aging resistance and low-temperature bending resistance of asphalt. However, due to the differences in structure, molecular weight, polarity, etc. between SBS and asphalt, SBS and asphalt undergo phase separation during long-term storage, resulting in substandard performance after 3 months or more. The double bonds in asphalt are easily reacted with oxygen, causing a sharp drop in the aging resistance of asphalt waterproofing membranes.
[0051] The inventors of the present application have found that, compared with the other aforementioned methods, the thiol click reaction is simple and easy to perform, has high selectivity, and produces no by-products.
[0052] In order to solve the problems of the prior art, the present application provides an SBS modifier and a preparation method and use thereof, an asphalt coating composition and a preparation method thereof, and a waterproofing membrane. The following first introduces the SBS modifier and a preparation method thereof provided in the present application.
[0053] Firstly, biomass carbon aerogel is prepared as the raw material for preparing SBS modifier.
[0054] Preparation of biochar aerogel
[0055] Preparation of biomass carbon aerogel, including:
[0056] B1, mixing the wood material and water according to a preset ratio and performing hydrothermal treatment to obtain a first product;
[0057] B2, washing and freezing the first product to obtain a frozen product;
[0058] B3. The frozen product is freeze-dried to obtain biomass carbon aerogel.
[0059] The biomass carbon aerogel prepared in the examples of the present application is in the form of solid powder.
[0060] In some embodiments of the present application, the wood material is selected from at least one of eucalyptus, pine, poplar, elm, willow, apricot, birch, maple, camphor, and shrubs, wherein the shrubs are selected from shrubs with branches or roots of wood fibers.
[0061] In an embodiment of the present application, a wood material and water are mixed in a preset ratio for hydrothermal treatment, including: mixing the wood material and water in a preset ratio to obtain a first mixture; adjusting the pH value of the first mixture to 8-12 and adding a crosslinking agent for dispersion, reacting at 180°C to 200°C for 8-12h, and obtaining a black carbon aerogel crude product, i.e., the first product. It should be noted that the water used to obtain the first mixture is distilled water.
[0062] In some embodiments of the present application, the preset ratio of the wood material to water is 1:(5-10). Exemplarily, the preset ratio of the wood material to water is 1:5.1, 1:5.15, 1:5.2, 1:5.5, 1:5.8, 1:6.0, 1:6.5, 1:6.8, 1:6.9, 1:7.0, 1:7.2, 1:7.5, 1:7.8, 1:8.0, 1:8.5, 1:8.8, 1:9.0, 1:9.3, 1:9.5, 1:9.8, 1:9.9.
[0063] In the embodiments of the present application, the crosslinking agent is epichlorohydrin or ethylene oxide. In addition to the epoxy group of epichlorohydrin in the crosslinking agent forming a covalent bond with the hydroxyl, amine, and carboxyl active groups in the wood material, the chloropropane group will undergo a substitution reaction with the nucleophilic substance or nucleophilic group in the wood material to generate a new compound with a crosslinked structure, thereby forming a macromolecular compound. The ethylene oxide in the crosslinking agent forms a covalent bond with the hydroxyl, amine, and carboxyl active groups in the wood material, and can also form a macromolecular compound with a certain molecular weight.
[0064] In some embodiments, the mass ratio of the crosslinking agent to the wood material is 1:(1.2-2). Exemplarily, the mass ratio of the crosslinking agent to the wood material is 1:1.25, 1:1.3, 1:1.35, 1:1.5, 1:1.6, 1:1.7, 1:1.75, 1:7.2, 1:1.8, 1:1.9, 1:1.95.
[0065] In an embodiment of the present application, the pH value of the first mixture can be adjusted to 8 to 12 by adding an alkaline compound to the first mixture. The alkaline compound is selected from alkali metal hydroxides or ammonia water. For example, sodium hydroxide, potassium hydroxide, and ammonia water can be added to adjust the pH value of the first mixture to 8, 8.5, 9, 9.7, 10, 10.5, 11, 11.5, and 12.
[0066] In an embodiment of the present application, washing the first product includes: washing the first product multiple times with distilled water, ethanol or isopropanol. That is, the first product is first washed multiple times with distilled water, and then washed multiple times with ethanol, or ethanol and isopropanol, or isopropanol, to remove excess alkali and solvent from the crude carbon aerogel product.
[0067] In some embodiments of the present application, the freezing temperature of the washed first product is -40°C to -10°C, and the freezing time is 15 hours to 30 hours.
[0068] In the embodiment of the present application, the first product after washing is frozen to maintain the original structure of the wood material. The frozen product is freeze-dried to rapidly vaporize the water in the wood material, and is not affected by surface tension during the freeze-drying process, so that the internal structure of the wood material can be well preserved, especially porous and easily collapsed materials, so that biomass carbon aerogel with a large specific surface area can be prepared.
[0069] Exemplarily, the preparation of biomass carbon aerogel includes: placing 6g to 10g of wood material, i.e., dry pine powder, in a 100ml beaker, adding 10ml to 12ml of deionized water to obtain a first mixture; adding 5ml to 8ml of a 2% to 5% NaOH solution to the first mixture, adjusting the pH value to 8 to 12, adding epichlorohydrin under magnetic stirring and stirring until the mixture is uniformly mixed, wherein the mass ratio of epichlorohydrin to wood material is 1:(1.2 to 2), transferring the obtained uniform mixture to a polytetrafluoroethylene hydrothermal reactor, reacting at 180°C to 200°C for 8 to 12h to obtain a black carbon aerogel crude product, i.e., the first product; washing the first product with distilled water and ethanol three times respectively, and then freezing the first product, the freezing temperature is -20°C to -10°C, and the freezing time is 20 hours to 25 hours to obtain a frozen product; placing the frozen product in a freeze dryer for freeze drying to obtain a biomass carbon aerogel.
[0070] Figure 1 The schematic diagram of the process for preparing the SBS modifier provided in the examples of the present application is shown.
[0071] Preparation of SBS modifier
[0072] The preparation method of SBS modifier comprises:
[0073] S1, dissolving SBS in a first solvent to obtain an SBS solution;
[0074] S2, adding a mercapto compound to the SBS solution, and carrying out solution graft polymerization at a temperature of 50°C to 90°C to obtain a graft-modified SBS, wherein the graft-modified SBS is grafted with an alkyl group containing either a hydroxyl group or a carboxyl group through a mercapto group, or a mercapto group and a hydroxyl-substituted or unsubstituted alkyl group through a mercapto group;
[0075] S3, adding the biomass carbon aerogel and the grafted modified SBS into the second solvent in a mass ratio of 1: (0.5-1.5) to obtain a first mixed solution;
[0076] S4. Add concentrated sulfuric acid and sodium hypophosphite to the first mixed solution, and react at a temperature of 120° C. to 130° C. to obtain an SBS modifier.
[0077] The preparation method of the SBS modifier of the embodiment of the present application changes the polarity of SBS by thiol grafting to obtain a grafted modified SBS, so that the grafted modified SBS is closer to the polarity of asphalt; the grafted modified SBS is then reacted with the biomass carbon aerogel to generate a macromolecular compound with a relatively stable structure, that is, an SBS modifier with stable performance and good durability is obtained, so as to prevent the performance of the waterproof membrane containing the SBS modifier from being significantly attenuated during the long-term aging process.
[0078] In some embodiments of the present application, SBS is a linear structure, and the weight average molecular weight of SBS (ethylene-butadiene-styrene triblock copolymer) is 100,000-450,000.
[0079] In some embodiments of the present application, the weight average molecular weight of SBS is preferably 150,000-300,000.
[0080] In some embodiments of the present application, the content of styrene segments in SBS is 20% to 30%, and the melt flow rate is 0 g / 10 min to 1 g / 10 min.
[0081] In some embodiments, the first solvent is selected from at least one of toluene, cyclohexane, CCl4, and CHCl3.
[0082] In some embodiments of the present application, the temperature of the first solvent is raised to 30°C to 50°C during the process of dissolving SBS in the first solvent to accelerate the dissolution rate of SBS. Optionally, the dissolution of SBS in the first solvent is carried out under the protection of an inert atmosphere. The inert atmosphere is formed by at least one selected from nitrogen, argon, and neon. For example, the inert atmosphere is formed by nitrogen alone.
[0083] In some embodiments of the present application, a thiol compound is added to the SBS solution, and a solution graft polymerization is carried out using an initiator at a temperature of 50° C. to 90° C.
[0084] In the examples of the present application, the amount of the initiator added is 0.5 wt % to 3 wt % of the mass of SBS.
[0085] In some embodiments of the present application, the initiator is azobisisobutyronitrile (AIBN). Optionally, the added amount of azobisisobutyronitrile (AIBN) is 0.5 wt % to 2 wt % of the mass of SBS.
[0086] In some embodiments of the present application, the process parameters that need to be met for solution graft polymerization of SBS solution and thiol compound are: rotation speed of 250 rpm to 350 rpm, and solution graft polymerization time of 1 hour to 2 hours.
[0087] In some embodiments of the present application, a thiol compound and an initiator are added to an SBS solution and the temperature is raised to 50° C. to 90° C. to perform solution graft polymerization to obtain a modified SBS mixed solution.
[0088] In some embodiments of the present application, the thiol compound is selected from at least one of mercaptoethanol, n-dodecyl mercaptan, and mercaptopropionic acid. Among them, the mercaptopropionic acid is selected from 2-mercaptopropionic acid, 3-mercaptopropionic acid, or a combination thereof. After the mercaptopropionic acid is grafted onto SBS through a thiol grafting reaction with the olefinic double bond of SBS, the thiol (-SH) and carboxyl (-COOH) contained in the grafted modified SBS can undergo an esterification reaction with the carboxyl (-COOH) and hydroxyl (-OH) contained in the biomass carbon aerogel to generate a macromolecular compound, thereby improving the stability of the asphalt coating and waterproofing membrane containing the SBS modifier.
[0089] In some embodiments of the present application, the mass ratio of SBS to the thiol compound is 20:(5-15). That is, the mass ratio of SBS to mercaptoethanol is 20:(5-15). Alternatively, the mass ratio of SBS to mercaptoethanol and n-dodecyl mercaptan is 20:(5-15). Alternatively, the mass ratio of SBS to n-dodecyl mercaptan is 20:(5-15), or the mass ratio of SBS to mercaptopropionic acid is 20:(5-15). Exemplarily, the mass ratio of SBS to mercaptoethanol, the mass ratio of SBS to mercaptoethanol and n-dodecyl mercaptan, the mass ratio of SBS to n-dodecyl mercaptan, and the mass ratio of SBS to mercaptopropionic acid can all be 20:5.5, 20:6, 20:7.2, 20:7.5, 20:7.8, 20:8, 20:9, 20:10, 20:12, 20:13.5, 20:14, 20:15.
[0090] In some embodiments of the present application, the preparation method of the grafted modified SBS further includes purifying the modified SBS mixed solution, including: dropping the modified SBS mixed solution into methanol for purification to obtain the grafted modified SBS with higher purity.
[0091] In some embodiments of the present application, the modified SBS mixed solution is dropped into methanol for purification, including: dropping the modified SBS mixed solution into methanol for precipitation, filtering, and drying, dissolving the dried product with a first solvent and repeating the steps of precipitation, filtering, and drying in methanol for multiple times, and drying the obtained target product to constant weight to obtain grafted modified SBS.
[0092] Illustratively, under nitrogen protection, 20 g of SBS is dissolved in 200 ml of toluene, and the toluene is heated to 50° C. to completely dissolve the SBS to obtain an SBS solution; 5 g to 15 g of mercaptoethanol and 0.1 wt.% to 2 wt.% of AIBN by mass of the SBS are added to the SBS solution, and the SBS solution with the mercaptoethanol and AIBN added is heated to 80° C. for reaction, and the solution graft polymerization is carried out at 80° C. and 250 rpm for 1 hour to 2 hours to obtain a modified SBS mixed solution; the modified SBS mixed solution is dropped into methanol for precipitation and filtration, and the filtered sample is vacuum dried at 70° C. for 12 hours to 15 hours; the dried sample is dissolved in toluene, and then precipitated in methanol, filtered, and vacuum dried in turn, the dried product is dissolved and the above precipitation, filtration, and vacuum drying steps are repeated 3 times, and the obtained product is placed in a 70° C. oven and dried to constant weight to obtain a grafted modified SBS. The mercaptoethanol can also be replaced by mercaptopropionic acid, n-dodecyl mercaptan, or a mixture of mercaptoethanol and n-dodecyl mercaptan, or a mixture of mercaptopropionic acid and n-dodecyl mercaptan. Optionally, in some embodiments, the content of mercaptopropionic acid can be partially excessive to avoid the reduction of mercaptopropionic acid due to self-polymerization of mercaptopropionic acid, or due to the polymerization of mercaptopropionic acid and mercaptoethanol, or due to the polymerization of mercaptopropionic acid and n-dodecyl mercaptan.
[0093] In the embodiment of the present application, SBS is mixed with mercaptoethanol, so that SBS is grafted with corresponding functional groups through mercapto groups to obtain grafted modified SBS by grafting alkyl groups containing hydroxyl groups, or grafting mercapto groups and grafting alkyl groups substituted with hydroxyl groups through mercapto groups, so that the hydroxyl groups or mercapto groups in the grafted modified SBS molecular structure can undergo esterification reaction with the carboxyl groups in the biomass carbon aerogel to form a macromolecular compound, namely, SBS modifier, so that the performance of the asphalt coating composition containing the SBS modifier is more stable. Exemplarily, SBS reacts with mercaptoethanol to generate a compound with the following structural formula:
[0094]
[0095] In formula (1) and formula (2), All represent the main chain skeleton of SBS. In some embodiments of the present application, mercaptoethanol is used as a modifier of SBS, and SBS and mercaptoethanol react to generate a graft-modified SBS in which an alkyl group containing a hydroxyl group is grafted onto a thiol group, or a graft-modified SBS containing a thiol group and an alkyl group substituted with a hydroxyl group is grafted onto a thiol group, so that the graft-modified SBS can undergo an esterification reaction with the carboxyl group in the biochar aerogel through the hydroxyl group or thiol group of its side chain to obtain a compound with a macromolecular structure, i.e., an SBS modifier.
[0096] In addition, SBS and mercaptoethanol and n-dodecyl mercaptan, or SBS and n-dodecyl mercaptan can react similarly, so that SBS can be grafted with mercapto groups to obtain a grafted modified SBS close to the polarity of asphalt, which can further react with biomass carbon aerogel to generate a covalently bonded macromolecular compound, making the asphalt coating containing SBS modifier more stable. It should be noted that since n-dodecyl mercaptan contains a mercapto group, after it is connected to the butadiene double bond of SBS through the mercapto group, the generated is an alkyl grafted by a mercapto group, or a grafted modified SBS grafted with a mercapto group and an alkyl grafted by a mercapto group. It can be understood that mercaptoethanol, mercaptoethanol, n-dodecyl mercaptan, and n-dodecyl mercaptan can be replaced by other alcohol compounds containing mercapto groups, and the activity of mercapto groups and alcoholic hydroxyl groups is relatively high. The mercapto group reacts with the double bond of the vinyl group in SBS under the action of the initiator and is grafted onto the SBS molecular chain. The alcoholic hydroxyl group reacts with the carboxyl group of the biomass carbon aerogel to obtain a macromolecular compound.
[0097] In other embodiments of the present application, the thiol compound can also be selected from at least one of 4-mercaptobutyric acid, 1-propanethiol, 1-butanethiol, phenylthiol, 1-pentanethiol, 1-hexanethiol, 2-phenylethanethiol, 2-bromothiophenol, 4-bromothiophenol, and 4-hydroxythiophenol. That is, mercaptoethanol can also be replaced by a combination of one or more of these thiol compounds.
[0098] In the embodiment of the present application, in the step of adding concentrated sulfuric acid and sodium hypophosphite to the first mixed solution, concentrated sulfuric acid is used as a catalyst to catalyze the reaction of biochar aerogel and grafted modified SBS, and the amount of concentrated sulfuric acid is 0.2% to 0.8% of the total mass of biochar aerogel and grafted modified SBS, and the mass concentration of concentrated sulfuric acid is 98% or more. Sodium hypophosphite is used to maintain the appearance of grafted modified SBS, and the amount is 0.05wt.% to 0.1wt.% of the mass of grafted modified SBS. Among them, the carboxyl group (-COOH) contained in the biochar aerogel can react with the hydroxyl group (-OH) or thiol group (-SH) of the grafted modified SBS to generate a relatively stable macromolecular compound, which prevents the performance of the waterproof membrane containing the SBS modifier from being significantly attenuated during long-term aging.
[0099] In some embodiments of the present application, biochar aerogel and grafted modified SBS are added to a second solvent at a mass ratio of 1:(0.5-1.5) and the temperature is raised to 50° C.-90° C. to promote the dissolution and dispersion of the grafted modified SBS.
[0100] In some embodiments, the second solvent is selected from dimethyl sulfoxide (DMSO), dimethylformamide (DMF).
[0101] In some embodiments, concentrated sulfuric acid and sodium hypophosphite are added to the first mixed solution, reacted at a temperature of 120° C. to 130° C., and heat-insulated under an inert atmosphere to obtain an SBS modifier.
[0102] In some embodiments, the process parameters required for the heat preservation treatment under an inert atmosphere are: a pressure of -80KPa to -50KPa, an inert atmosphere, and a heat preservation treatment time of 2.5 hours to 4 hours. The inert atmosphere is formed by at least one selected from nitrogen, argon, and neon. For example, the inert atmosphere is formed by nitrogen.
[0103] In some embodiments of the present application, the preparation method of the SBS modifier further includes: dropping the first mixed solution to which concentrated sulfuric acid and sodium hypophosphite are added and heat-insulated into methanol for precipitation, filtering, and drying, re-dissolving the first purified product with a second solvent and repeating the steps of precipitation, filtering, and drying for multiple times, and drying the obtained target product to a constant weight to obtain the SBS modifier. The first mixed solution is in liquid form after the heat-insulation treatment, and the product after the heat-insulation treatment needs to be purified.
[0104] The preparation method of the SBS modifier of the embodiment of the present application is to generate a relatively stable macromolecular compound, namely, the SBS modifier, by reacting the grafted modified SBS with the biomass carbon aerogel, so as to prevent the performance of the waterproofing membrane containing the SBS modifier from being significantly attenuated during the long-term aging process. Among them, the macromolecular compound is more stable in structure and is not easy to phase separate in the formulation of the asphalt coating composition.
[0105] The SBS modifier of the embodiment of the present application can reduce its own polarity and make it compatible with asphalt molecules through the thiol-grafted ethylene or dodecyl part, thereby preventing phase separation due to the different polarities of the components of the asphalt coating composition; the biomass carbon aerogel part can improve the anti-aging performance of the waterproof membrane by utilizing its own good heat resistance and heat insulation properties, and at the same time, utilize its own powdery structure to increase the physical entanglement with the asphalt molecules, thereby increasing the resistance to phase separation and preventing the waterproof membrane from phase separation.
[0106] SBS Modifier
[0107] The SBS modifier of the embodiment of the present application is prepared according to the preparation method of the above-mentioned SBS modifier. The SBS modifier of the embodiment of the present application is generated by esterification reaction of grafted modified SBS with biomass carbon aerogel to generate a macromolecular compound with a relatively stable structure, that is, an SBS modifier with stable performance and good durability, which prevents the performance of the waterproof membrane containing the SBS modifier from being significantly attenuated during the long-term aging process.
[0108] In the examples of the present application, the SBS modifier obtained by reacting the biomass carbon aerogel in solid powder form with the grafted modified SBS is still in solid powder form.
[0109] Application of SBS modifier
[0110] In some embodiments of the present application, a SBS modifier is provided for use in asphalt modification, so as to make the asphalt have good stability and prevent phase separation.
[0111] Asphalt coating composition
[0112] The embodiments of the present application also provide an asphalt coating composition, comprising the following raw materials with rubber addition percentage (PHR): asphalt, 100PHR; asphalt softening oil, 5PHR~10PHR; SBS modifier, 3PHR~5PHR; SBS modifier is an SBS modifier prepared according to the above-mentioned SBS modifier preparation method; SBR modifier, 2PHR~4PHR; rubber powder, 30PHR~50PHR; powder, 50PHR~70PHR.
[0113] In some embodiments of the present application, the asphalt is selected from 70# asphalt, 90# asphalt or a combination thereof.
[0114] In some embodiments, the asphalt softening oil is selected from at least one of naphthenic oil, soybean oil, and aromatic oil.
[0115] In some embodiments of the present application, the rubber powder is 60-80 mesh tire rubber powder, the rubber content is 30%-50%, and the ash content is 10%-30%.
[0116] In some embodiments, the powder is selected from heavy calcium powder and talcum powder, and the particle size is 200 mesh to 400 mesh.
[0117] Method for preparing asphalt coating composition
[0118] Figure 2 A schematic flow chart of a method for preparing an asphalt coating composition provided in an embodiment of the present application is shown.
[0119] A method for preparing an asphalt coating composition comprises:
[0120] C1. Mixing asphalt and asphalt softening oil according to the ratio of the asphalt coating material composition to obtain a first mixture;
[0121] C2, heating the first mixture until the asphalt is completely melted, adding SBS modifier and SBR modifier to the first mixture for dispersion, and obtaining a second mixture;
[0122] C3, adding rubber powder to the second mixture for dispersion to obtain a third mixture;
[0123] C4. Add powder to the third mixture for dispersion to obtain an asphalt coating material composition.
[0124] In some embodiments, the mixture of asphalt and asphalt softening oil is heated to 130° C. to 150° C. to melt all the 70# asphalt.
[0125] In some embodiments of the present application, the SBS modifier and the SBR modifier are added to the first mixture for dispersion and the temperature can be raised to 160° C. to 180° C. and kept warm for 1 hour to 1.5 hours.
[0126] In some embodiments, rubber powder is added to the second mixture and the temperature is raised to 180° C. to 190° C. for dispersion.
[0127] In some embodiments of the present application, rubber powder is added to the second mixture, the temperature is raised to 180° C. to 190° C., and the mixture is dispersed at 500 rpm to 800 rpm for 3 to 4 hours.
[0128] In some embodiments, powder is added to the third mixed material and dispersed at 180°C to 190°C.
[0129] In some embodiments of the present application, powder is added to the third mixed material and dispersed at 180° C. to 190° C. and 800 rpm to 1000 rpm for 1 hour to 2 hours.
[0130] Waterproof membrane
[0131] like Figure 3 As shown, an embodiment of the present application also provides a waterproof roll material, including a main substrate; and an asphalt coating layer arranged on at least one side surface of the main substrate, the asphalt coating layer is formed by applying the above-mentioned asphalt coating composition on at least one side surface of the main substrate.
[0132] In some embodiments, the waterproof membrane further includes an isolation protective layer covering the asphalt coating layer.
[0133] In some embodiments, the main substrate is made of a reinforcing material. The main substrate is selected from polyester, glass fiber or polyester glass fiber. The isolation protective layer is a single-sided release film made of transparent PET material with a thickness of 0.001mm to 0.035mm, which is coated with solvent-free silicone oil and has a release force of 0.1N / 25mm to 0.5N / 25mm.
[0134] In the embodiments of the present application, the SBS modifier improves the stability of the waterproofing membrane during long-term storage. On the one hand, the SBS modifier obtained after the SBS is modified is stably present in the asphalt coating composition, making the SBS modifier and the asphalt component compatible to prevent phase separation. On the other hand, biochar aerogel is an aging-resistant material that is resistant to high and low temperatures and has relatively stable performance. When the SBS modifier and the biochar aerogel are used together in the asphalt coating composition, the performance of the waterproofing membrane containing the asphalt coating composition can be effectively prevented from attenuating in a short period of time.
[0135] Test Section
[0136] The following are the brands / models or available sources of some raw materials and reagents: SBS, brand 411, manufacturer Yueyang Baling Petrochemical. SBR modifier, brand 095, manufacturer Yueyang Baling Petrochemical. Asphalt softening oil, cyclohexane oil, soybean oil, aromatic oil; rubber powder, 60-80 mesh tire rubber powder, in which the mass content of rubber is 30%-50%, and the ash content is 10%-30%, the manufacturer is Sanming Hongyuan; mercaptoethanol, purchased from Sinopharm Chemical Reagent Co., Ltd.; azobisisobutyronitrile (AIBN), purchased from Shandong Huayu Chemical Technology Co., Ltd.
[0137] Preparation of biochar aerogel
[0138] 10 g of wood material (dried pine powder and eucalyptus powder in a mass ratio of 1:1) and distilled water in a mass ratio of 10:12 are mixed to obtain a first mixture; a NaOH solution with a mass fraction of 2.5% is added to the first mixture, the pH value of the first mixture is adjusted to 9, 6.66 g of epichlorohydrin is added under magnetic stirring and stirred until the mixture is uniformly mixed, the obtained uniform mixture is transferred to a stainless steel reactor with a polytetrafluoroethylene liner, and after being completely sealed, the stainless steel reactor is placed in an electric blast drying oven for hydrothermal treatment at 200° C. The reaction time of the hydrothermal treatment is 12 hours, and then naturally cooled to room temperature to obtain a first product.
[0139] The first product was washed three times with distilled water and ethanol respectively, and then placed in a refrigerator and frozen at -15°C for 24 hours to obtain a frozen product as a sample; the frozen sample was placed in a freeze dryer to dry, and biomass carbon aerogel was obtained.
[0140] Preparation of Graft-Modified SBS
[0141] Preparation of grafted modified SBS (N1): Under nitrogen protection, 20 g of SBS was dissolved in 200 ml of toluene, and the temperature was raised to 50° C. to completely dissolve the SBS to obtain an SBS solution; 5 g of mercaptoethanol and 1.0% AIBN by weight of the SBS were added to the SBS solution, and the SBS solution with the mercaptoethanol and AIBN added was heated to 80° C. for reaction, and solution graft polymerization was carried out at 80° C. and 250 rpm for 1 hour to obtain a modified SBS mixed solution; the modified SBS mixed solution was dropped into methanol for precipitation and filtration, and the filtered sample was vacuum dried at 70° C. for 12 hours; the dried sample was dissolved in toluene, and then precipitation, filtration, and vacuum drying were carried out in sequence, and the above precipitation, filtration, and vacuum drying steps were repeated 3 times, and the obtained product was placed in a 70° C. oven and dried to constant weight to obtain a grafted modified SBS, and the grafted modified SBS grafted with thiol was recorded as N1.
[0142] Preparation of grafted modified SBS (N2): Under nitrogen protection, 20g of SBS was dissolved in 200ml of toluene, and the temperature was raised to 50°C to completely dissolve the SBS to obtain an SBS solution; 10g of mercaptoethanol and 1.0% AIBN by mass of SBS were added to the SBS solution, and the SBS solution with the addition of mercaptoethanol and AIBN was heated to 80°C for reaction, and solution graft polymerization was carried out at 80°C and 250rpm for 1 hour to obtain a modified SBS mixed solution; the modified SBS mixed solution was dropped into methanol for precipitation and filtration, and the filtered sample was vacuum dried at 70°C for 12 hours; the dried sample was dissolved in toluene, and then precipitation, filtration, and vacuum drying were carried out in sequence, and the above precipitation, filtration, and vacuum drying steps were repeated 3 times, and the resulting product was placed in a 70°C oven and dried to constant weight to obtain a grafted modified SBS, and the grafted modified SBS grafted thiol was recorded as N2.
[0143] Preparation of grafted modified SBS (N3): Under nitrogen protection, 20g of SBS was dissolved in 200ml of toluene, and the temperature was raised to 50°C to completely dissolve the SBS to obtain an SBS solution; 15g of mercaptoethanol and 1.0% AIBN by mass of the SBS were added to the SBS solution, and the SBS solution with the addition of mercaptoethanol and AIBN was heated to 80°C for reaction, and solution graft polymerization was carried out at 80°C and 250rpm for 1 hour to obtain a modified SBS mixed solution; the modified SBS mixed solution was dropped into methanol for precipitation and filtration, and the filtered sample was vacuum dried at 70°C for 12 hours; the dried sample was dissolved in toluene, and then precipitation, filtration, and vacuum drying were carried out in sequence, and the above precipitation, filtration, and vacuum drying steps were repeated 3 times, and the resulting product was placed in a 70°C oven and dried to constant weight to obtain a grafted modified SBS, and the grafted modified SBS grafted with thiol was recorded as N3.
[0144] Preparation of SBS modifier
[0145] Grafted modified SBS labeled N1, N2, and N3 were weighed respectively, and added to dimethyl sulfoxide with the biomass carbon aerogel prepared as above in a mass ratio of 1:1, heated to 50°C and stirred until there was no solid matter, to obtain first mixed solutions respectively; the same amount of concentrated sulfuric acid and sodium hypophosphite were slowly added to each first mixed solution, and the temperature was continued to be raised to 120°C to 125°C, and nitrogen was introduced under vacuum -80KPa for 2.5 hours. After the reaction was completed, mixed solutions of SBS modifiers were obtained respectively; the mixed solutions of SBS modifiers were precipitated and filtered respectively, and the filtered products were dried to obtain SBS modifiers respectively, which were recorded as W1, W2, and W3.
[0146] Example 1
[0147] A waterproof roll material comprises: a main substrate, an asphalt coating layer disposed on at least one side of the main substrate, and an isolation protective layer covering the asphalt coating layer. The asphalt coating layer is formed by coating the above-mentioned asphalt coating composition (including W1) on one side of the main substrate. The asphalt coating composition is made of the following raw materials with the following rubber addition percentage (PHR): 70# asphalt, 100PHR; asphalt softening oil, 5PHR; SBS modifier (W1), 3PHR; SBR modifier, 4PHR; rubber powder, 30PHR; heavy calcium, 70PHR.
[0148] The preparation method of the asphalt coating composition comprises: mixing 70# asphalt and asphalt softening oil at a rotation speed of 1000 rpm according to the ratio of the asphalt coating composition, heating to 140°C-145°C, and keeping the temperature for 1.5 hours to melt the 70# asphalt completely, so as to obtain a first mixture; adding SBS modifier (W1) and SBR modifier to the first mixture, heating to 170°C-180°C for dispersion, and keeping the temperature for 1.5 hours to obtain a second mixture; adding rubber powder to the second mixture, heating to 180°C-190°C, and shearing and dispersing at a rotation speed of 800 rpm for 2.5 hours to obtain a third mixture; adding powder to the third mixture, and shearing and dispersing at 180°C-185°C at a rotation speed of 1000 rpm for 1.5 hours to obtain an asphalt coating composition.
[0149] Example 2
[0150] A waterproof roll material comprises: a main substrate, an asphalt coating layer disposed on at least one side of the main substrate, and an isolation protective layer covering the asphalt coating layer. The asphalt coating layer is formed by coating the above-mentioned asphalt coating composition (including W2) on one side of the main substrate. The asphalt coating composition is made of the following raw materials with the following rubber addition percentage (PHR): 70# asphalt, 100PHR; asphalt softening oil, 5PHR; SBS modifier (W2), 3PHR; SBR modifier, 4PHR; rubber powder, 30PHR; heavy calcium, 70PHR.
[0151] The preparation method of the asphalt coating composition comprises: mixing 70# asphalt and asphalt softening oil at a rotation speed of 1000 rpm according to the ratio of the asphalt coating composition, heating to 140°C-145°C, and keeping warm for 1.5 hours to make the 70# asphalt completely melt, so as to obtain a first mixture; adding SBS modifier (W2) and SBR modifier to the first mixture, heating to 170°C-180°C for dispersion, and keeping warm for 1.5 hours to obtain a second mixture; adding rubber powder to the second mixture, heating to 180°C-190°C, and shearing and dispersing at a rotation speed of 800 rpm for 2.5 hours to obtain a third mixture; adding powder to the third mixture, and shearing and dispersing at 180°C-185°C at a rotation speed of 1000 rpm for 1.5 hours to obtain an asphalt coating composition.
[0152] Example 3
[0153] A waterproofing coiled material comprises: a main substrate, an asphalt coating layer disposed on at least one side of the main substrate, and an isolation protective layer covering the asphalt coating layer. The asphalt coating layer is formed by coating the above-mentioned asphalt coating composition (including W3) on one side of the main substrate. The asphalt coating composition is made of the following raw materials with the following rubber addition percentage (PHR): 70# asphalt, 100PHR; asphalt softening oil, 5PHR; SBS modifier (W3), 3PHR; SBR modifier, 4PHR; rubber powder, 30PHR; heavy calcium, 70PHR.
[0154] The preparation method of the asphalt coating composition comprises: mixing 70# asphalt and asphalt softening oil at a rotation speed of 1000 rpm according to the ratio of the asphalt coating composition, heating to 140°C-145°C, and keeping warm for 1.5 hours to make the 70# asphalt completely melt, so as to obtain a first mixture; adding SBS modifier (W3) and SBR modifier to the first mixture, heating to 170°C-180°C for dispersion, and keeping warm for 1.5 hours to obtain a second mixture; adding rubber powder to the second mixture, heating to 180°C-190°C, and shearing and dispersing at a rotation speed of 800 rpm for 2.5 hours to obtain a third mixture; adding powder to the third mixture, and shearing and dispersing at 180°C-185°C at a rotation speed of 1000 rpm for 1.5 hours to obtain an asphalt coating composition.
[0155] Example 4
[0156] A waterproofing coiled material comprises: a main substrate, an asphalt coating layer disposed on at least one side of the main substrate, and an isolation protective layer covering the asphalt coating layer. The asphalt coating layer is formed by coating the above-mentioned asphalt coating composition (including W3) on one side of the main substrate. The asphalt coating composition is made of the following raw materials with the following rubber addition percentage (PHR): 70# asphalt, 100PHR; asphalt softening oil, 5PHR; SBS modifier (W3), 4PHR; SBR modifier, 4PHR; rubber powder, 30PHR; heavy calcium, 70PHR.
[0157] The preparation method of the asphalt coating composition comprises: mixing 70# asphalt and asphalt softening oil at a rotation speed of 1000 rpm according to the ratio of the asphalt coating composition, heating to 140°C-145°C, and keeping warm for 1.5 hours to make the 70# asphalt completely melt, so as to obtain a first mixture; adding SBS modifier (W3) and SBR modifier to the first mixture, heating to 170°C-180°C for dispersion, and keeping warm for 1.5 hours to obtain a second mixture; adding rubber powder to the second mixture, heating to 180°C-190°C, and shearing and dispersing at a rotation speed of 800 rpm for 2.5 hours to obtain a third mixture; adding powder to the third mixture, and shearing and dispersing at 180°C-185°C at a rotation speed of 1000 rpm for 1.5 hours to obtain an asphalt coating composition.
[0158] Example 5
[0159] A waterproofing coiled material comprises: a main substrate, an asphalt coating layer disposed on at least one side of the main substrate, and an isolation protective layer covering the asphalt coating layer. The asphalt coating layer is formed by coating the above-mentioned asphalt coating composition (including W3) on one side of the main substrate. The asphalt coating composition is made of the following raw materials with the following rubber addition percentage (PHR): 70# asphalt, 100PHR; asphalt softening oil, 5PHR; SBS modifier (W3), 5PHR; SBR modifier, 4PHR; rubber powder, 30PHR; heavy calcium, 70PHR.
[0160] The preparation method of the asphalt coating composition comprises: mixing 70# asphalt and asphalt softening oil at a rotation speed of 1000 rpm according to the ratio of the asphalt coating composition, heating to 140°C-145°C, and keeping warm for 1.5 hours to make the 70# asphalt completely melt, so as to obtain a first mixture; adding SBS modifier (W3) and SBR modifier to the first mixture, heating to 170°C-180°C for dispersion, and keeping warm for 1.5 hours to obtain a second mixture; adding rubber powder to the second mixture, heating to 180°C-190°C, and shearing and dispersing at a rotation speed of 800 rpm for 2.5 hours to obtain a third mixture; adding powder to the third mixture, and shearing and dispersing at 180°C-185°C at a rotation speed of 1000 rpm for 1.5 hours to obtain an asphalt coating composition.
[0161] Comparative Example 1
[0162] A waterproofing coiled material comprises: a main substrate, an asphalt coating layer disposed on at least one side of the main substrate, and an isolation protective layer covering the asphalt coating layer. The asphalt coating layer is formed by coating the above-mentioned asphalt coating composition on one side of the main substrate. The asphalt coating composition is made of the following raw materials with the following rubber addition percentage (PHR): 70# asphalt, 100PHR; asphalt softening oil, 5PHR; SBS, 5PHR; wherein the SBS is not modified; SBR modifier, 4PHR; rubber powder, 30PHR; heavy calcium, 70PHR.
[0163] The preparation method of the asphalt coating composition comprises: mixing 70# asphalt and asphalt softening oil at a rotation speed of 1000 rpm according to the ratio of the asphalt coating composition, heating to 140°C-145°C, and keeping warm for 1.5 hours to make the 70# asphalt completely melt, so as to obtain a first mixture; adding SBS and SBR modifiers to the first mixture, heating to 170°C-180°C for dispersion, and keeping warm for 1.5 hours to obtain a second mixture; adding rubber powder to the second mixture, heating to 180°C-190°C, and shearing and dispersing at a rotation speed of 800 rpm for 2.5 hours to obtain a third mixture; adding powder to the third mixture, and shearing and dispersing at 180°C-185°C at a rotation speed of 1000 rpm for 1.5 hours to obtain an asphalt coating composition.
[0164] Comparative Example 2
[0165] A waterproofing coiled material comprises: a main substrate, an asphalt coating layer disposed on at least one side of the main substrate, and an isolation protective layer covering the asphalt coating layer. The asphalt coating layer is formed by coating the above-mentioned asphalt coating composition on one side of the main substrate. The asphalt coating composition is made of the following raw materials with the following rubber addition percentage (PHR): 70# asphalt, 100PHR; asphalt softening oil, 5PHR; grafted modified SBS (N1), 5PHR; SBR, 4PHR; rubber powder, 30PHR; heavy calcium, 70PHR.
[0166] The preparation method of the asphalt coating composition comprises: mixing 70# asphalt and asphalt softening oil at a rotation speed of 1000 rpm according to the ratio of the asphalt coating composition, heating to 140°C-145°C, and keeping the temperature for 1.5 hours to make the 70# asphalt completely melt, so as to obtain a first mixture; adding grafted modified SBS (N1) and SBR modifier to the first mixture, heating to 170°C-180°C for dispersion, and keeping the temperature for 1.5 hours to obtain a second mixture; adding rubber powder to the second mixture, heating to 180°C-190°C, and shearing and dispersing at a rotation speed of 800 rpm for 2.5 hours to obtain a third mixture; adding powder to the third mixture, and shearing and dispersing at 180°C-185°C at a rotation speed of 1000 rpm for 1.5 hours to obtain an asphalt coating composition.
[0167] Performance Testing
[0168] The waterproof membranes of Examples 1-5 and Comparative Examples 1-2 were subjected to the following performance tests, and the test data were recorded in Table 1:
[0169] 1. Low temperature flexibility test before and after aging
[0170] The aging conditions used for waterproof membranes are: aging in a forced air oven at a heat aging temperature of 70°C for 7 days and 14 days. The low-temperature flexibility test method used for waterproof membranes is carried out in accordance with the national standard GB / T 328-2007 "Test Methods for Building Waterproof Membrane" Part 14 for sample preparation and testing. Among them, the low-temperature flexibility limit test is carried out on the waterproof membrane after aging for 7 days and 14 days respectively. It should be noted that the low-temperature limit can characterize the durability of the waterproof membrane containing the SBS modifier. The lower the low-temperature limit temperature, the better the durability of the waterproof membrane.
[0171] 2. Peel strength test of aluminum plate used for waterproof membrane
[0172] According to the national standard GB 23442-2009 "Self-adhesive polymer modified bitumen waterproofing membrane", the sample is prepared and the aluminum plate peeling strength is tested. Among them, the aluminum plate peeling strength takes the maximum value.
[0173] Table 1
[0174]
[0175] Combining the components of Examples 1-5 and Comparative Examples 1-2, by comparing the test data of low temperature flexibility and peel strength of the waterproof membranes of the Examples and Comparative Examples, it can be seen that:
[0176] The asphalt coating composition of the waterproofing membrane of Comparative Example 1 contains unmodified SBS. The low temperature limit of the low temperature flexibility of the waterproofing membrane before aging is -26°C and the peeling strength is 2.09N / mm; the low temperature limit after aging for 7 days is -17°C and the peeling strength is 1.53N / mm. The low temperature attenuation after aging for 7 days is 34.62% and the peeling strength decreases by 26.79%. The low temperature limit after aging for 14 days is -14°C and the low temperature attenuation is 46.51%. The peeling strength after aging for 14 days is still 1.53N / mm and the peeling strength decreases by 26.79%. The above test data show that the peeling strength and aging strength of the waterproofing membrane before and after aging for 7 days and 14 days are not linearly related, but the low temperature limit performance of the waterproofing membrane is obviously affected by the aging strength.
[0177] The asphalt coating composition of the waterproofing membrane of Comparative Example 2 contains grafted modified SBS. The low temperature limit of the low temperature flexibility of the waterproofing membrane before aging is -27°C and the peeling strength is 1.98N / mm. The low temperature limit after aging for 7 days is -22°C and the peeling strength is 1.87N / mm. The low temperature limit attenuation after aging for 7 days is 18.52%, and the peeling strength decreases by 5.56%. The low temperature limit after aging for 14 days is -18°C, the low temperature limit attenuation is 33.33%, and the peeling strength after aging for 14 days is 1.74N / mm, and the peeling strength decreases by 12.12%. The above test data show that the peeling strength and aging strength of the waterproofing membrane before and after aging for 7 days and 14 days are not linearly related, but the low temperature limit performance of the waterproofing membrane is obviously affected by the aging strength.
[0178] The extreme low temperature flexibility, peeling strength and attenuation amplitude of the waterproofing membrane in comparative example 2 in which SBS is modified by grafting thiol groups are better than the extreme low temperature flexibility, peeling strength and attenuation amplitude of the waterproofing membrane in comparative example 1 in which SBS is not modified. The extreme low temperature flexibility, peeling strength and attenuation amplitude of the waterproofing membrane containing SBS modifier in Example 5 are better than the extreme low temperature flexibility, peeling strength and their respective performance attenuation amplitude of the waterproofing membrane in comparative example 2 in which only SBS is modified by grafting thiol groups. The test results of Example 5 and comparative examples 1 and 2 show that the extreme low temperature flexibility, peeling strength and their respective performance attenuation amplitude of the waterproofing membrane in which SBS is modified by grafting thiol groups and reacted with biomass carbon aerogel to prepare SBS modifier are better than the extreme low temperature flexibility and peeling strength of the waterproofing membrane in which only SBS is modified by grafting thiol groups, and have a lower performance attenuation amplitude.
[0179] By comparing the waterproofing membranes of Examples 1-3, it can be concluded that with the increase of the corresponding structural units of mercaptoethanol in the SBS modifier, the low-temperature flexibility attenuation amplitude of the waterproofing membrane decreases, and the peel strength of the waterproofing membrane increases. With the relative increase in the amount of SBS modifier containing the highest content of mercaptoethanol structural units in Examples 4 and 5, the low-temperature flexibility attenuation amplitude of the waterproofing membranes of Examples 4 and 5 is significantly reduced, and the extreme low temperature is kept at -24°C to -27°C, and the peel strength reduction of the waterproofing membrane is gradually reduced. It shows that increasing the amount of SBS modifier used in the examples of this application can effectively enhance the aging resistance of the waterproofing membrane and improve the problem of phase separation.
[0180] The low-temperature flexibility limit temperature of the waterproof membrane of Example 5 before aging is -28°C, the low-temperature flexibility limit temperature after aging for 7 days is -27°C, and the low-temperature performance attenuation is only 3.57%; the low-temperature flexibility limit temperature after aging for 14 days is -25°C, and the low-temperature performance attenuation is only 10.71%; and the peel strength attenuation after aging for 7 days and after aging for 14 days is the smallest, both of which are 3.32%; This indicates that the waterproof membrane of the asphalt coating composition that meets the ratio of Example 5 has good aging resistance, and thus has a longer low-temperature flexibility attenuation resistance and a lower peel strength drop, so that the waterproof membrane can be more stably stored, transported and served.
[0181] The asphalt coating composition of the waterproofing membrane of Examples 1-5 of the present application contains an SBS modifier treated by the reaction of biomass carbon aerogel and grafted modified SBS. The low temperature limit of the low temperature flexibility of the waterproofing membrane before aging is -26°C at the highest, -28°C at the lowest, and the lowest peel strength is 1.89N / mm; the maximum low temperature limit after aging for 7 days is -19°C, the lowest peel strength is 1.69N / mm, the maximum attenuation of the extreme low temperature after aging for 7 days is 26.92%, and the maximum reduction of the peel strength is 10.58%. The maximum low temperature limit after aging for 14 days is -14°C, the maximum attenuation of the extreme low temperature is 46.51%, the minimum peel strength after aging for 14 days is 1.58N / mm, and the maximum reduction of the peel strength is 16.58%. That is, the maximum attenuation amplitude of the extreme low temperature performance of the waterproofing membrane after aging for 14 days in 1-5 is 46.51%, and its peeling strength after aging for 14 days is also stronger than the peeling strength value of the waterproofing membrane in Comparative Example 1 as a whole, and the maximum reduction amplitude of the peeling strength is 16.58%, which are significantly smaller than the extreme low temperature attenuation amplitude and peeling strength attenuation amplitude of the waterproofing membrane in Comparative Example 1 without SBS modification. Only the low temperature performance attenuation amplitude of the waterproofing membrane in Example 1 and Example 2 after aging for 14 days is higher than the low temperature performance attenuation amplitude of the waterproofing membrane in Comparative Example 2 after aging for 14 days, and only the peeling strength attenuation amplitude of the waterproofing membrane in Example 1 and Example 2 after aging for 14 days is higher than the peeling strength attenuation amplitude of the waterproofing membrane in Comparative Example 2 including only SBS grafting modification. The above test data show that the peeling strength and aging strength of the waterproofing membrane before and after aging for 7 days and 14 days are not linearly related, but the extreme low temperature performance of the waterproofing membrane is obviously affected by the aging strength.
[0182] The above data test results of the waterproofing membranes of Examples 1-5 can prove that the overall low-temperature flexibility of the waterproofing membranes containing SBS modifiers prepared in the examples of the present application is better than that of the existing waterproofing membranes, and the attenuation of the extreme low-temperature performance after aging for 7 days and 14 days is relatively low, the peel strength is relatively high, and the reduction in peel strength is also relatively small overall. Therefore, the test results of the extreme low-temperature performance and the aging peel strength show that the asphalt coating composition containing SBS modifiers in the present application can prevent the performance of the waterproofing membrane from being significantly attenuated during the long-term aging process.
[0183] The inventors of this application found that the polarity of asphalt itself is very small, which is quite different from the polarity of SBS. In the initial stage, it is simply physically and mechanically mixed. After a period of storage, asphalt and SBS will separate, making the coil unable to achieve long-term stability. The SBS modifier obtained by the reaction of biomass carbon aerogel and grafted modified SBS in this application changes the polarity of SBS, increases the compatibility of asphalt and SBS modifier, and can maintain high product performance during production, transportation, storage and service.
[0184] The SBS modifier of the present application, on the one hand, can be stably present in the asphalt coating composition after the SBS is modified, and on the other hand, the biomass carbon aerogel is an aging-resistant material that is resistant to high and low temperatures and has relatively stable performance. The two raw materials are stably combined and applied to the asphalt coating composition to prevent the performance of the asphalt coating from degrading in a short period of time, thereby preventing the waterproof membrane from phase separation and solving the problem of a sharp decline in aging resistance.
[0185] The above is only a specific implementation method of the present application. Those skilled in the art can clearly understand that for the convenience and simplicity of description, the specific working process described above can refer to the corresponding process in the aforementioned method embodiment, and will not be repeated here. It should be understood that the protection scope of the present application is not limited to this. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application.
Claims
1. A method for preparing a SBS modifier, characterized in that: include: dissolving SBS in a first solvent to obtain an SBS solution; Adding a mercapto compound to the SBS solution, and performing solution graft polymerization at a temperature of 50° C. to 90° C. to obtain a graft-modified SBS, wherein the graft-modified SBS is grafted with an alkyl group containing at least one of a hydroxyl group and a carboxyl group through a mercapto group, or grafted with a mercapto group and a hydroxyl-substituted or unsubstituted alkyl group through a mercapto group; Adding the biomass carbon aerogel and the grafted modified SBS into the second solvent in a mass ratio of 1:(0.5-1.5) to obtain a first mixed solution; Concentrated sulfuric acid and sodium hypophosphite are added to the first mixed solution, and the mixture is reacted at a temperature of 120° C. to 130° C. to obtain an SBS modifier.
2. The method for preparing the SBS modifier according to claim 1, characterized in that: Meet at least one of the following requirements: The SBS has a linear structure, and the weight average molecular weight of the SBS is 100,000 to 450,000; The first solvent is selected from at least one of toluene, cyclohexane, CCl4, and CHCl3; Dissolving the SBS in the first solvent under the protection of an inert atmosphere; In the process of dissolving the SBS in the first solvent, the temperature of the first solvent is raised to 30° C. to 50° C. to accelerate the dissolution of the SBS; The mass ratio of the SBS to the thiol compound is 20:(5-15); The thiol compound is added to the SBS solution, and solution graft polymerization is performed using an initiator at a temperature of 50° C. to 90° C.; Add the biomass carbon aerogel and the grafted modified SBS in a mass ratio of 1:(0.5-1.5) into a second solvent and heat it to 50° C.-90° C.; The thiol compound is selected from at least one of mercaptoethanol, n-dodecyl mercaptan, and mercaptopropionic acid; The second solvent is selected from dimethyl sulfoxide and dimethylformamide; The concentrated sulfuric acid and sodium hypophosphite are added to the first mixed solution to react at a temperature of 120° C. to 130° C., and the mixture is heat-insulated in an inert atmosphere to obtain an SBS modifier.
3. The preparation method of the SBS modifier according to claim 2, characterized in that, Meet at least one of the following requirements: The weight average molecular weight of the SBS is 150,000 to 300,000; The content of styrene segments in the SBS is 20% to 30%; the melt flow rate is 0g / 10min to 1g / 10min; The amount of the initiator added is 0.5wt% to 3wt% of the mass of the SBS; The initiator is azobisisobutyronitrile; The inert atmosphere is formed by at least one selected from nitrogen, argon and neon; The process parameters that need to be met for the heat preservation treatment under an inert atmosphere are: a pressure of -80KPa to -50KPa, an inert atmosphere, and a heat preservation treatment time of 2.5 hours to 4 hours.
4. The method for preparing the SBS modifier according to claim 1, characterized in that: The biomass carbon aerogel in the step of obtaining the first mixed solution is prepared by the following steps: Mixing the wood material and water according to a preset ratio and performing hydrothermal treatment to obtain a first product; Washing and freezing the first product to obtain a frozen product; The frozen product is freeze-dried to obtain biomass carbon aerogel.
5. The method for preparing the SBS modifier according to claim 4, characterized in that: The step of mixing the wood material and water according to a preset ratio for hydrothermal treatment comprises: Mixing the wood material and water according to a preset ratio to obtain a first mixture; The pH value of the first mixture is adjusted to 8-12, a cross-linking agent is added for dispersion, and the mixture is reacted at 180° C. to 200° C. to obtain a first product; wherein the mass ratio of the cross-linking agent to the wood material is 1:(1.2-2).
6. The method for preparing the SBS modifier according to claim 4 or 5, characterized in that: Meet any one of the following requirements: The wood material is selected from at least one of eucalyptus, pine, poplar, elm, willow, apricot, birch, maple, camphor and shrub chips; The preset ratio of the wood material to water is 1:(5-10) by mass.
7. A SBS modifier, characterized in that The SBS modifier is prepared according to the preparation method of any one of claims 1 to 6.
8. Use of the SBS modifier as claimed in claim 7 for asphalt modification.
9. An asphalt coating composition, characterized in that: Including the following raw materials with rubber addition percentage: Asphalt, 100PHR; Asphalt softening oil, 5PHR~10PHR; SBS modifier, 3PHR to 5PHR, wherein the SBS modifier is the SBS modifier according to claim 7; SBR modifier, 2PHR~4PHR; Rubber powder, 30PHR~50PHR; Powder, 50PHR~70PHR.
10. The asphalt coating composition according to claim 9, characterized in that: Meet at least one of the following requirements: The asphalt is selected from 70# asphalt, 90# asphalt or a combination thereof; The asphalt softening oil is at least one of naphthenic oil, soybean oil and aromatic oil; The rubber powder is 60-80 mesh tire rubber powder, with a rubber content of 30%-50% and an ash content of 10%-30%; The powder is selected from heavy calcium powder and talcum powder, and the particle size is 200-400 meshes.
11. A method for preparing the asphalt coating composition according to claim 9 or 10, characterized in that: include: The asphalt and asphalt softening oil are mixed according to the ratio of the asphalt coating material composition to obtain a first mixture; The first mixture is heated until the asphalt is completely melted, and the SBS modifier and the SBR modifier are added to the first mixture for dispersion to obtain a second mixture; adding the rubber powder to the second mixed material for dispersion to obtain a third mixed material; The powder is added to the third mixture for dispersion to obtain an asphalt coating composition.
12. The method for preparing the asphalt coating composition according to claim 11, characterized in that: Meet at least one of the following requirements: Heating the first mixture to 130° C. to 150° C. to melt all the asphalt; The SBS modifier and the SBR modifier are added to the first mixed material for dispersion and the temperature can be raised to 160° C. to 180° C.; adding the rubber powder into the second mixture and heating it to 180° C. to 190° C. for dispersion; The powder is added to the third mixed material and dispersed at 180° C. to 190° C.
13. A waterproof roll material, characterized in that: include: Main substrate; And an asphalt coating layer is arranged on at least one side of the surface of the main substrate, and the asphalt coating layer is formed by coating the asphalt coating composition according to claim 9 or 10 on at least one side of the surface of the main substrate.
Citation Information
Patent Citations
Method for modifying styrene-butadiene-styrene (SBS) block copolymer
CN102391424A
Branched chain functionalized styrene-butadiene-styrene block copolymer (SBS) and preparation method thereof as well as application of branched chain functionalized SBS in modified asphalt
CN106496467A
Modified SBS elastomer, preparation method, asphalt coating material and waterproof coiled material
CN115181225A
Porous carbon polymer / block copolymer modified asphalt as well as preparation method and application thereof
CN116285400A
Biomass flame-retardant heat-insulating self-adhesive waterproof coiled material and preparation method thereof
CN117736666A
Cited By
Bio-based non-cured asphalt waterproof coating and preparation method thereof
CN120098549A
Bio-based non-curing asphaltic waterproof coating and method for preparing the same
CN120098549B
Preparation method of high-stability SBS modified asphalt
CN122427533A
